Destination as Product Placement: An Advertising Strategy to Impact Beliefs and Behavioral Intentions. Issue 3 (26th May 2020) - Jung, Eunkyeong; Childs, Michelle
Abstract: This study identified the effect of destination placement (present vs. absent) on consumers' responses to the place and branded product and the subsequent effect on consumers' intention to visit the destination and purchase the brand, respectively in order to establish how a destination may effectively collaborate with a brand as part of their advertising. Results demonstrated the presence of a destination positively influences both destination and product beliefs. Also, this study found that consumers' familiarity with the destination in the branded advertisement can enhance the relationship between destination placement and destination beliefs and product beliefs. Lastly, results showed that consumers' beliefs about a particular destination positively influence their visit intentions, and consumers' beliefs about a branded product positively affect their purchase intention.